Variabel Moderasi dalam Preferensi Konsumen Film Indonesia - Nur Hadiyazid Rachman (Universitas Muhammadiyah Tangerang, 2021)
On various international film festival, it is not uncommon indonesian movie prestigious receives the award. But, Indonesian movies have not been able to be a master in their own homes to lack of appreciation. The indonesian movie number of spectators not comparable with the audience foreign film. As the product of industrial, film need marketing, in an unconventional manner the film industry of the need a network of a movie theater.The purpose of this research are: the first, to analyzing the factors that influence preference of consumers the indonesian movie viewing of the decision in a movie theater. Second, to know variable moderation is that influence preference of consumers the indonesian movie viewing of the decision in a movie theater. Third, to know the interaction of factors variable moderation and an explanatory variable that influence preference of consumers the indonesian movies viewing of the decision in a movie theater.Based on the analysis of SEM-PLS be concluded that: the first, variable that influence the indonesian movie viewing decision are the product, promotion, and the age of the audience. Second, the gender variable only can be used as it pure-moderation. Third, variable the age of the audience can be used as an explanatory variable and variable moderation simultaneously in analysis (quasi-moderation).